2020
DOI: 10.1021/acsanm.0c00319
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Ligand Selection on the Formation of Metal Phosphonate-Derived CoMoP and CoMoP2 Nanoparticles for Catalytic Hydrogen Evolution

Abstract: Coordination polymers (CPs) and metal–organic frameworks (MOFs) have emerged as versatile precursors for transition-metal phosphides catalysts. However, the controlled synthesis of CPs-derived bimetallic phosphides remains a challenge, as mixtures of various phosphide phases are often formed. Here, it is shown that controlling the formation of pure CoMoP and CoMoP2 nanoparticles requires a careful choice of the ligands used to construct the precursors based on the chemical properties of the metals. In particul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…Metal phosphonates were chosen as precursors to benefit from the homogeneous distribution of the metals across the phosphonate network, which can promote a homogeneous distribution of the dopants after pyrolysis. [7,29] The effect of each dopant on the chemical, physical and electrochemical properties of MoP was first studied separately. The optimum amounts of dopants were then selected to design the dual-doped catalysts, which were subsequently investigated in depth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal phosphonates were chosen as precursors to benefit from the homogeneous distribution of the metals across the phosphonate network, which can promote a homogeneous distribution of the dopants after pyrolysis. [7,29] The effect of each dopant on the chemical, physical and electrochemical properties of MoP was first studied separately. The optimum amounts of dopants were then selected to design the dual-doped catalysts, which were subsequently investigated in depth.…”
Section: Resultsmentioning
confidence: 99%
“…[2,6] Transition-metal phosphides (TMPs) are a promising alternative to Pt, owing to their high HER activity in acid electrolytes, high conductivity and facile synthesis routes. [7][8][9][10] Molybdenum phosphide (MoP) has recently been the focus of intense investigations as a HER catalyst. [11,12] However, its activity in acidic media is still inferior to that of the Pt/C benchmark, and it is unsatisfactorily low in alkaline media.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Xu et al 41 reported a series of metal phosphidesbased pre-catalysts by phosphidation process with different metal components (M = Fe, Co, Ni). The OER 42,67,[109][110][111][112] Metal phosphates have emerged as promising electrocatalysts owing to their structural stability. Previous studies indicate that phosphates group can facilitate the oxidation of metal atoms and act as proton acceptors to make the catalysts more favorable for water adsorption and oxidation.…”
Section: Metal Phosphides and Phosphatesmentioning
confidence: 99%
“…The OER activities followed the order of FeCoNiP > CoNiP > FeNiP > FeCoP > CoP, where the intrinsic OER activity was related to the number of transition metal species. Besides, some dual‐doped metal phosphide catalysts such as Fe‐doped CoP, Co 2 P‐Ni 2 P, Fe‐doped Ni 2 P, Mo‐doped Ni 2 P, and NiCoP have been reported as bifunctional catalysts with exceptional OER and HER activity 42,67,109‐112 …”
Section: Precious‐metal‐free Electrocatalystsmentioning
confidence: 99%
“…[147,[148][149][150] Porous metal phosphonate hybrids have been widely used as highly promising materials in numerous energy-storage reactions (e.g., Li-ion battery, fuel cells, and supercapacitors). [151][152][153][154][155] Porous metal phosphonate electrodes have the following remarkable properties: i) the predefined molecular redox functional groups can be flexibly integrated into pore walls or on the surface to control the redox potential; ii) the well-structured nanopores facilitate the intercalation/deintercalation of electrolyte ions;…”
Section: Electrochemical Energy Storagementioning
confidence: 99%